The Students’ Attitude toward English Learning at Seventh Grade of SMP Swasta Kristen Tomosa 1 - Fister Handayanti Zai; Hidayati Daeli; Yasminar Amaerita Telaumbanua; Riswan Zega (Raja Zulkarnain Education Foundation, 2026)
his study aims to analyze students' attitudes toward learning English reading in seventh-grade students at Tomosa 1 Private Christian Junior High School. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, questionnaires, and documentation. The study subjects consisted of 38 seventh-grade students and one English teacher. Data analysis was conducted in four stages: data collection, data reduction, data presentation, and conclusion drawing and verification. The results showed that most students had positive attitudes toward learning English reading. This was evident from their active involvement in reading texts, their willingness to answer questions based on the reading, and their efforts to understand vocabulary and text content. However, several students also exhibited negative attitudes, such as a lack of interest in reading English texts, difficulty understanding the reading content, and a tendency to be passive during the reading activity. Factors influencing students' attitudes toward learning English reading include family environment, peer influence, unsupervised use of gadgets, the teacher's reading learning methods, and students' perceptions of the difficulty level of English reading texts. In addition, this study found that the application of interesting reading strategies, the use of texts that are appropriate to students' ability levels, the integration of character education, providing motivation, and increasing interaction between teachers and students are effective in building students' positive attitudes towards reading activities.